Trademark Protection as a Preventive Tool for Combating Counterfeit Goods and Preserving Consumer Confidence in Indonesia - Hulman Panjaitan; Andrew Betlehn (Greenation International Journal of Law and Social Sciences, 2026)
This study examines the role of trademark protection as a preventive legal mechanism for combating counterfeit products and preserving consumer confidence in Indonesia. Using a qualitative descriptive approach based on literature review and regulatory analysis, the research explores the relationship between trademark protection, consumer rights, and the effectiveness of preventive legal measures within the Indonesian legal framework. The analysis focuses on regulatory provisions, implementation practices, consumer perceptions, institutional enforcement, and structural challenges affecting trademark protection. The findings reveal that trademark protection performs a dual function: safeguarding the exclusive rights of trademark owners while simultaneously reducing consumer exposure to counterfeit goods. The study argues that the preventive value of trademark protection extends beyond intellectual property enforcement by serving as a mechanism for maintaining product authenticity, market transparency, and consumer confidence. However, the effectiveness of this function is constrained by weak legal awareness, inconsistent enforcement, limited inter-agency coordination, and the increasing sophistication of counterfeit distribution channels. The analysis further demonstrates that consumer trust is closely linked to the credibility of trademark protection, making effective enforcement an essential element of consumer welfare and fair market competition. This study contributes to the literature by positioning trademark protection not only as an intellectual property regime but also as a preventive consumer protection instrument. It concludes that strengthening trademark enforcement and institutional coordination is essential to enhance consumer confidence and reduce the circulation of counterfeit products in Indonesia.